Meningkatkan Hasil Belajar menggunakan Tipe Jigsaw pada Materi Jaringan Tumbuhan Siswa Kelas VIII SMPN 2 Pematang Karau dengan Media Leaflet - Amir Amir; Muhammad Zain (Universitas Sebelas Maret, 2017)
Classroom action research was conducted at SMP Negeri 2 Pematang Karau Pematang Karau Subdistrict, East Barito Regency. Problems experienced by teachers is on the learning process has not been maximized. There are 33 students of class VIII SMP Negeri 2 Pematang Karau, 8 students of whom are willing to interact actively. Learning outcomes average grade VIII students was 45. Whereas Minimum Competence Score is 75. This study result to improve learning outcomes using Jigsaw Type cooperative model on the topic of Plant systematics. The study was conducted two cycles. Based on the results it can be concuded that the implementation of Jigsaw cooperative learning can improve learning outcomes